2018
DOI: 10.1002/ldr.2924
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the extent of cropland abandonment in mountainous regions of China

Abstract: With the wages for migrant workers increasing dramatically in China since 2003, the size of the agricultural labour forces has been shrinking rapidly. Intensively substituting agricultural machinery for the shrinking farm labour force is hardly possible for croplands in the mountainous regions of China where mechanization is difficult to achieve due to small field size and rough terrain. This has eventually led to cropland abandonment in these regions. Considering the high pressure for food security in China, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 80 publications
3
91
2
2
Order By: Relevance
“…Farmland abandonment in the mountainous regions is expected to increase in the future [24,38]. One study found that a total of 28% farmland was abandoned from 2000 to 2010 in China's mountainous areas, where farmlands were freely abandoned by farmer for the Grain for Green project (1999) to convert farmland to forest or grassland to mitigate soil erosion in the sloping Mountain region of China [19]. China and Nepal have a similar Mountain region topography in the China-Nepal border region, although the percentages of farmland abandonment rates are different due to policy and decision of household level.…”
Section: Farmland Abandonment In Different Physiographic Regionsmentioning
confidence: 99%
“…Farmland abandonment in the mountainous regions is expected to increase in the future [24,38]. One study found that a total of 28% farmland was abandoned from 2000 to 2010 in China's mountainous areas, where farmlands were freely abandoned by farmer for the Grain for Green project (1999) to convert farmland to forest or grassland to mitigate soil erosion in the sloping Mountain region of China [19]. China and Nepal have a similar Mountain region topography in the China-Nepal border region, although the percentages of farmland abandonment rates are different due to policy and decision of household level.…”
Section: Farmland Abandonment In Different Physiographic Regionsmentioning
confidence: 99%
“…However, in recent years, farmland abandonment has also occurred in developing countries [8][9][10]. For example, in China, the world's largest developing country, some 12-15% of rural farmland was abandoned between 2013 and 2015 [11][12][13]. In addition, China is becoming rapidly urbanized, such that the phenomenon of farmland abandonment in rural China may become more common in the future.…”
Section: Introductionmentioning
confidence: 99%
“…It is lower than that of other studies. The RFA reached 0.29 in Wushan, Chongqing [49], the values were 0.37 and 0.25 in Gansu Province and Tianjin [1] respectively, while an estimation of the national RFA in mountainous counties of China reached 0.28 [50], and the average RFA was 0.29 in Three Gorges Reservoir Area [22]. There might be four reasons for this difference.…”
Section: Discussionmentioning
confidence: 95%